Wheat Cost-Return Budget in Northeast Kansas - O'Brien, Daniel M.; Duncan, Stewart R. (My University, 2012)
This publication projects a budget that reflects expected income and costs based on wheat production in northeastern Kansas.
MF572_2012_12
Keywords: MF572; Economics; Crops; MF